Protective effect of umbilical cord mesenchymal stem cells combined with resveratrol against renal podocyte damage in NOD mice. (October 2019) - Xian, Yuxin; Lin, Yi; Cao, Caixia; Li, Li; Wang, Jing; Niu, Jiapeng; Guo, Yunlei; Sun, Yanan; Wang, Yangang; Wang, Wei
Highlights: Human umbilical cord mesenchymal stem cells are abundant and easy to obtain. Studies suggested resveratrol could enhance the function of mesenchymal stem cells. The role of RAGE-NF-кB signaling pathway in podocyte inflammation has not been reported. Abstract: Background: The role of chronic inflammation initiated by persistent hyperglycemia in podocyte injury has attracted increasing attention. The advanced glycation end products (RAGE) receptor- nuclear factor-kappa B (NF-кB) signaling pathway is involved in the occurrence of inflammation. We speculate that treatment with human umbilical cord mesenchymal stem cells (hUCMSCs) combined with resveratrol can block this signaling pathway and protect podocyte function. Methods: Non obesity diabetes(NOD) mice were randomly divided into 5 groups: NOD-T1DM, Res, hUCMSCs, hUCMSCs + Res and insulin (INS)groups. Mice without diabetes were classified as NOD control group(NOD group). Blood glucose(BG), blood urea nitrogen(BUN), serum creatinine(SCr), 24-h urine albumin excretion rate (UAER) were measured. The expression of nephrin, WT1 and RAGE, MCP-1 in renal tissues were detected by Western blot, expression of NF-кB protein(P65) was determined by immunohistochemistry. Results: The combined treatment of hUCMSCs and Resveratrol can reduce BG, BUN, SCr, 24-h UAER, and the expression of the inflammatory factors MCP-1, RAGE and NF-кB; increase the number of podocytes and the expression of the podocyte-related proteins nephrin and WT1 in type 1 diabetes mellitus, and improve renal pathological structure. Conclusions: Combining of hUCMSCs and resveratrol can better protect renal podocyte function, and the effects on the reduction of blood glucose and renal injury are better than those obtained by insulin treatment. This indicated that the combination of Res and hUCMSCs may be a novel therapeutic method for the treatment of DN.